2016
DOI: 10.1002/cmdc.201600083
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Studies around the Mono‐ and Difunctionalization of a Bioavailable Cyclic Decapeptide Scaffold

Abstract: We previously reported the design of several cyclic decapeptides based on a generic scaffold that achieved favorable oral bioavailability and exposure. With the goal to further investigate the potential of this approach, we describe herein the effect of mono- and difunctionalization of this scaffold. A series of cyclic decapeptides were therefore subjected to a range of in vitro assays and pharmacokinetic (PK) studies to investigate whether the introduction of polar or charged groups could be tolerated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…We designed two cyclic peptomer scaffolds based on aseries of highly cell permeable and orally bioavailable cyclic decapeptides. [10] Va riants of this scaffold such as 1 (Figure 1a) are similar to the natural product gramicidin Si nw hich solvent-exposed amides are capped with N-methyl groups.Nmethylation eliminates the desolvation penalty associated with exposed backbone amides while preserving the intramolecular hydrogen bonding network of the natural product. TheF ouchØ peptide also shares the same pattern of stereocenters and overall architecture as the previously described cyclic hexapeptide 1NMe3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We designed two cyclic peptomer scaffolds based on aseries of highly cell permeable and orally bioavailable cyclic decapeptides. [10] Va riants of this scaffold such as 1 (Figure 1a) are similar to the natural product gramicidin Si nw hich solvent-exposed amides are capped with N-methyl groups.Nmethylation eliminates the desolvation penalty associated with exposed backbone amides while preserving the intramolecular hydrogen bonding network of the natural product. TheF ouchØ peptide also shares the same pattern of stereocenters and overall architecture as the previously described cyclic hexapeptide 1NMe3.…”
Section: Resultsmentioning
confidence: 99%
“…[15] LPE, defined specifically by the equation LPE = logD(dd/ w)À1.06AlogP + 5.47, represents as caffoldsi ntrinsic membrane permeability by normalizing its membrane partitioning against its bulk lipophilicity. [10] Compound 1 is aside-chain variant with exceptional oral bioavailability (> 100 %). b) Peptoid (X 1 and X 2 )a nd peptide (X 3 ) building blocks used in the synthesis of Libraries Aand B. c, d) Designs for cyclic peptomer Libraries A( c) and…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrated how multiple N -methylation and matched hydrogen bond pairs across the macrocycle (White et al 2011 ; Nielsen et al 2014 ; Fouche et al 2016a , b ) could improve oral bioavailability. In this study, we have shown how hydrophobic shielding can contribute to masking polarity, and thereby enhancing permeability, while simultaneously providing excellent solubility.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a publication appeared, which according to cellular tests did not support the 2-Pal residue as a suitable modification, but in this case no in vivo studies were performed (Thansandote et al 2015). While this more systematic work was in progress, our colleagues published on positive effects of 2-Pal modified cyclic decamers with respects to oral uptake (Fouche et al 2016). Since fine-tuning of properties is of particular importance for macromolecules designed for oral bioavailability, we decided to study various Pal residues incorporated in the same cyclic hexapeptide scaffold in more detail.…”
Section: Introductionmentioning
confidence: 99%